Present and Future of Allogeneic Natural Killer Cell Therapy - Lim, Okjae; Jung, Mi Young; Hwang, Yu Kyeong; Shin, Eui-Cheol (Frontiers in Immunology, 2015)
Natural killer (NK) cells are innate lymphocytes that are capable of eliminating tumor cells and are therefore used for cancer therapy. Although many early investigators used autologous NK cells, including lymphokine-activated killer cells, the clinical efficacies were not satisfactory. Meanwhile, human leukocyte antigen (HLA)-haploidentical hematopoietic stem cell transplantation revealed the antitumor effect of allogeneic NK cells, and HLA-haploidentical, killer cell immunoglobulin-like receptor ligand-mismatched allogeneic NK cells are currently used for many protocols requiring NK cells. Moreover, allogeneic NK cells from non-HLA-related healthy donors have been recently used in cancer therapy. The use of allogeneic NK cells from non-HLA-related healthy donors allows the selection of donor NK cells with higher flexibility and to prepare expanded, cryopreserved NK cells for instant administration without delay for ex vivo expansion. In cancer therapy with allogeneic NK cells, optimal matching of donors and recipients is important to maximize the efficacy of the therapy. In this review, we summarize the present state of allogeneic NK cell therapy and its future directions.